Metropolitan Migrants : The Migration of Urban Mexicans to the United States - Hernández-León, Ruben (Book collections on Project MUSE., 2008)
Challenging many common perceptions, this book is dedicated to understanding a major new phenomenon - the large number of skilled urban workers who are coming to America from Mexico's cities. Based on a ten-year study of one working-class neighbourhood in Monterrey, the book studies the forces that lead to Mexican emigration.